Lanthanum-containing silver alloy and preparation method and application thereof
By preparing silver alloys containing Cu, La, and Ag, and using specific temperatures and extrusion processes to form fine dispersed phases, the problems of insufficient yield strength and hardness of existing silver alloys were solved, and high-performance silver alloy materials were realized.
Patent Information
- Application Number
- CN202511161940.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-19
- Publication Date
- 2025-11-21
AI Technical Summary
Existing silver alloys contain a wide variety of elements, but the yield strength and hardness properties of Cu, La, and Ag alloys have not been addressed.
A silver alloy with the chemical composition CuxLayAgbal containing Cu, La, and Ag is prepared by melting at 800–970℃, holding at 850–1100℃, and hot extruding at 400–550℃ to form a fine and dispersed La-rich strengthening phase, thereby improving the yield strength and hardness of the alloy.
A lanthanum-containing silver alloy with a yield strength greater than or equal to 236 MPa and a hardness greater than or equal to 110 HBW was obtained, which significantly improved the mechanical properties of the alloy.
Smart Images

Figure CN120989450A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a lanthanum-containing silver alloy, its preparation method, and its uses. Background Technology
[0002] Silver alloys are alloys composed of silver as a base metal and other metals. Due to their excellent electrical and thermal conductivity, silver alloys have important applications in fields such as medicine, electrical contact materials, and aerospace.
[0003] CN119426846A discloses an active solder for sealing sapphire and Kovar alloy and its preparation method. The active solder contains 25.0–27.5 wt% Cu, 1.0–6.0 wt% Ti, 1.0–5.0 wt% Al, 0.1–1.0 wt% B, and 0.1–0.5 wt% rare earth element RE, where RE is one or more of La, Ce, Sc, Pr, Nd, and Er, with the balance being Ag. The preparation method includes: preparing silver-based pre-alloyed powder using gas atomization; mixing the alloy powder with additive element powder by ball milling; obtaining an alloy ingot by vacuum pressure sintering; and obtaining an active solder strip with a thickness of 0.05–0.2 mm through rough rolling, intermediate annealing, and finish rolling.
[0004] CN107109530A discloses a sliding contact material having the following composition: 6.0% to 9.0% by mass of Cu, 0.1% to 2.0% by mass of Ni, 0.1% to 0.8% by mass of additive element M, and the balance being Ag. The additive element M is at least one element selected from the group consisting of Sm, La, and Zr. The sliding contact material of this document has a microstructure in which dispersed particles containing intermetallic compounds containing at least Ni and additive element M are dispersed within an Ag alloy matrix.
[0005] CN119772450A discloses an AgCuNi multi-element brazing filler metal, which is composed of the following components by mass percentage: Ni 5-15%, Sn 1-5%, Zn 1-5%, In 1-5%, La 0-1%, Bi 0-1%, with the balance being Ag and Cu in a mass ratio of 68-76:24-32. The disclosure also includes a method for preparing the AgCuNi multi-element brazing filler metal and a brazing process. The raw materials are melted, rolled, annealed, and thinned to obtain the AgCuNi multi-element brazing filler metal. Subsequently, the filler metal is assembled with tantalum and Q345R steel to form a brazing component and then vacuum brazed.
[0006] The above literature uses a wide variety of elements, not just alloys of Cu, La and Ag, and does not cover yield strength and hardness properties. Summary of the Invention
[0007] In view of this, one object of the present invention is to provide a silver alloy containing only lanthanum, which contains only Cu, La and Ag, and has good yield strength and hardness.
[0008] Another object of the present invention is to provide a method for preparing a silver alloy containing lanthanum.
[0009] Another object of the present invention is to provide the use of lanthanum metal in improving the yield strength and hardness of silver alloys.
[0010] The present invention achieves the above objectives using the following technical solutions.
[0011] On the one hand, the present invention provides a silver alloy containing lanthanum, having a chemical composition as shown in formula (1):
[0012] Cu x La y Ag bal (1);
[0013] In formula (1), x is the weight percentage of Cu, which is 4 to 14 wt%; y is the weight percentage of La, which is 0.01 to 1 wt%; and bal indicates that Ag is the balance.
[0014] In the lanthanum-containing silver alloy according to the present invention, preferably, x is 5-12 wt% and y is 0.05-0.8 wt%.
[0015] In the lanthanum-containing silver alloy according to the present invention, preferably, x is 5-10 wt% and y is 0.1-0.6 wt%.
[0016] In the lanthanum-containing silver alloy according to the present invention, preferably, x is 5.5 to 8.5 wt% and y is 0.1 to 0.5 wt%.
[0017] In the lanthanum-containing silver alloy according to the present invention, preferably, x is 6-8 wt% and y is 0.15-0.35 wt%.
[0018] On the other hand, the present invention also provides a method for preparing a lanthanum-containing silver alloy according to the above description, comprising the following steps:
[0019] 1) Prepare raw materials of pure silver, pure copper, and lanthanum metal according to the composition of the silver alloy containing lanthanum;
[0020] 2) Melt pure silver and pure copper at 800-970℃ and remove surface slag to obtain a preliminary melt; add lanthanum metal to the preliminary melt, then raise the temperature to 850-1100℃ and hold at 850-1100℃ for 30-70 minutes to obtain a final melt; cast the final melt to obtain an alloy ingot.
[0021] 3) The obtained alloy ingot is hot-extruded at 400-550℃, extrusion ratio of 6-10:1, and extrusion rate of 4-9.5 mm / min to obtain the silver alloy containing lanthanum.
[0022] According to the preparation method of the present invention, preferably, the following step is further included between step 1) and step 2): preheating pure silver, pure copper and lanthanum metal at 180-270°C for 30-70 min respectively to obtain preheated pure silver, pure copper and lanthanum metal respectively.
[0023] According to the preparation method of the present invention, preferably, in step 2), before casting the final melt into the casting mold, the casting mold is preheated to 250-350°C.
[0024] According to the preparation method of the present invention, preferably, in step 3), the extrusion ratio is 7 to 9:1 and the extrusion rate is 5 to 8.5 mm / min.
[0025] Furthermore, the present invention also provides the use of lanthanum metal in improving the yield strength and hardness of silver alloys.
[0026] The lanthanum-containing silver alloy of the present invention exhibits high yield strength and hardness. The preparation method of the present invention is more advantageous for obtaining lanthanum-containing silver alloys with high yield strength and hardness. Attached Figure Description
[0027] Figure 1 This is a SEM image of the lanthanum-containing silver alloy obtained in Example 1.
[0028] Figure 2 The image shows the XRD pattern of the lanthanum-containing silver alloy obtained in Example 1. Detailed Implementation
[0029] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.
[0030] <Lanthium-containing silver alloy>
[0031] The present invention provides a lanthanum-containing silver alloy containing only Ag, Cu, and La. It may contain unavoidable impurities. It does not contain Ni, B, Ti, or Al. The lanthanum-containing silver alloy of the present invention exhibits high yield strength and hardness. This lanthanum-containing silver alloy has the chemical composition shown in formula (1):
[0032] Cu x La y Ag bal (1);
[0033] In equation (1), x is the weight percentage of Cu, ranging from 4 to 14 wt%; y is the weight percentage of La, ranging from 0.01 to 1 wt%; and bal indicates that Ag is in the balance. This lanthanum-containing silver alloy exhibits further improvements in both yield strength and hardness.
[0034] In formula (1), Cu is copper, and x is the weight percentage of Cu. x can be 4 to 14 wt%, preferably 5 to 12 wt%, more preferably 5 to 10 wt%, even more preferably 5.5 to 8.5 wt%, and even more preferably 6 to 8 wt%, for example, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, and 8 wt%.
[0035] In formula (1), La is lanthanum, y is the weight percentage of La, and y can be 0.01 to 1 wt%, preferably 0.05 to 0.8 wt%, more preferably 0.1 to 0.6 wt%, even more preferably 0.1 to 0.5 wt%, and even more preferably 0.15 to 0.35 wt%, for example, 0.15 wt%, 0.2 wt%, 0.25 wt%, 0.3 wt%, and 0.35 wt%.
[0036] In equation (1), Ag is the balance.
[0037] According to one embodiment of the present invention, the lanthanum-containing silver alloy has a chemical composition as shown in formula (1): Cu x La y Ag bal (1); In formula (1), x is the weight percentage of Cu element, x is 5 to 11 wt%; y is the weight percentage of La element, y is 0.05 to 0.8 wt%; bal indicates that Ag element is in the balance.
[0038] According to a specific embodiment of the present invention, the lanthanum-containing silver alloy has a chemical composition as shown in formula (1): Cu x La y Ag bal (1); In formula (1), x is the weight percentage of Cu element, x is 7 to 8 wt%; y is the weight percentage of La element, y is 0.2 to 0.3 wt%; bal indicates that Ag element is in the balance.
[0039] The lanthanum-containing silver alloy of the present invention has a yield strength greater than or equal to 236 MPa, preferably greater than or equal to 238 MPa, and up to 240 MPa; and a hardness greater than or equal to 110 HBW, and up to 112 HBW. A hardness greater than or equal to 110 HBW indicates a Brinell hardness value greater than or equal to 110.
[0040] <Preparation method of lanthanum-containing silver alloy>
[0041] The method for preparing the lanthanum-containing silver alloy of the present invention may include the following steps: 1) raw material preparation; 2) melt formation and casting; and 3) hot extrusion. These are described in detail below.
[0042] Raw material preparation steps
[0043] The raw materials are prepared according to the specific composition of the lanthanum-containing silver alloy as described above. The raw materials are pure silver, pure copper, and lanthanum metal. Pure silver can be pure silver ingots, pure silver powder, or pure silver rods; pure copper can be pure copper ingots, pure copper powder, or pure copper rods. Lanthanum metal can be lanthanum powder or lanthanum blocks. Pure silver refers to silver with a purity greater than or equal to 99.9%, preferably greater than 99.9%. Pure copper refers to copper with a purity greater than or equal to 99.9%, preferably greater than 99.9%. Lanthanum has a purity greater than 99%, preferably greater than or equal to 99.9%.
[0044] Melt formation and casting steps
[0045] Pure silver and pure copper are melted at 800–970℃, and surface slag is removed to obtain a preliminary melt. Lanthanum metal is added to the preliminary melt, and the temperature is then raised to 850–1100℃ and held at 850–1100℃ for 30–70 minutes to obtain a final melt. The final melt is then cast to obtain an alloy ingot. This process helps to improve the yield strength and hardness of the resulting lanthanum-containing silver alloy.
[0046] In this invention, pure silver, pure copper, and lanthanum metal can be preheated at 180–270°C for later use. The preheating temperature can be 180–270°C, preferably 190–250°C, and more preferably 200–230°C. This helps to remove moisture from the surfaces of the pure silver, pure copper, and lanthanum metal, thus avoiding affecting the strength and hardness of the final product.
[0047] In this invention, preheating can be performed in an inert atmosphere. The inert atmosphere can be one or more of nitrogen, neon, helium, and argon. According to one embodiment of the invention, preheating is performed in an argon atmosphere.
[0048] In this invention, preheated pure silver and pure copper are first melted. The raw materials can be placed in a melting container, such as a crucible, for example a graphite crucible. The graphite crucible containing the raw materials is then placed in a resistance furnace. According to a specific embodiment of the invention, the preheated pure silver and pure copper are melted in a resistance furnace, and surface slag is removed (without adding a slagging agent) to obtain a preliminary melt. The melting temperature can be 800–970°C, preferably 820–950°C, and more preferably 850–950°C. A certain vacuum degree can be maintained during melting, which can be less than 50 Pa, preferably less than 10 Pa, and more preferably less than or equal to 1 Pa.
[0049] In this invention, lanthanum metal is added to the initial melt, then the temperature is raised to 850–1100°C and held at 850–1100°C for 30–70 minutes to obtain the final melt. The final melt is then cast to obtain an alloy ingot. The holding temperature can be 850–1100°C, preferably 900–1000°C, and more preferably 950–980°C. The holding time can be 30–70 minutes, preferably 30–60 minutes, for example, 30 minutes, 40 minutes, 50 minutes, or 60 minutes. This is beneficial for improving the yield strength and hardness of the obtained lanthanum-containing silver alloy.
[0050] In this invention, the casting mold can be preheated to 250–350°C before casting the final melt. The preheating temperature is preferably 280–350°C, more preferably 300–330°C. This is beneficial for obtaining a lanthanum-containing silver alloy with good hardness.
[0051] Hot extrusion steps
[0052] The resulting alloy ingot is hot-extruded at 400–550°C, an extrusion ratio of 6–10:1, and an extrusion rate of 4–9.5 mm / min to obtain the lanthanum-containing silver alloy. This method helps to ensure that the lanthanum-containing silver alloy has higher yield strength and hardness.
[0053] In this invention, the hot extrusion temperature can be 400–550°C, preferably 430–540°C, and more preferably 450–520°C. The extrusion ratio can be 6–10:1, preferably 7–9:1, and more preferably 8–9:1. The extrusion rate can be 4–9.5 mm / min, preferably 5–8.5 mm / min, and more preferably 6–7 mm / min. Controlling the above parameters within the above ranges is more conducive to obtaining lanthanum-containing silver alloys with better yield strength and hardness.
[0054] In this invention, the extrusion ratio refers to the ratio of the cross-sectional area of the extrusion cylinder cavity to the total cross-sectional area of the extruded product, also known as the extrusion coefficient. The extrusion ratio is a parameter used in extrusion production to represent the amount of metal deformation.
[0055] In this invention, the lanthanum-containing silver alloy obtained by hot extrusion is a bar with a diameter of 12-16 mm, preferably 13-15 mm, and more preferably 14-15 mm.
[0056] According to a specific embodiment of the present invention, the method for preparing the lanthanum-containing silver alloy of the present invention includes the following steps:
[0057] 1) Prepare raw materials of pure silver, pure copper, and lanthanum metal according to the composition of the silver alloy containing lanthanum;
[0058] 2) Preheat pure silver, pure copper, and lanthanum metal to 180–270°C for later use; melt the preheated pure silver and pure copper at 800–970°C and remove surface slag to obtain a preliminary melt; add lanthanum metal to the preliminary melt, then raise the temperature to 850–1100°C and hold at 850–1100°C for 30–70 minutes to obtain a final melt; cast the final melt into a casting mold preheated to 250–350°C to obtain an alloy ingot.
[0059] 3) The alloy ingot obtained above is hot-extruded at 400–550°C, an extrusion ratio of 6–10:1, and an extrusion rate of 4–9.5 mm / min to obtain the lanthanum-containing silver alloy. This is beneficial for obtaining a lanthanum-containing silver alloy with higher yield strength and hardness.
[0060] <Application>
[0061] This invention also provides the use of lanthanum metal in improving the yield strength and hardness of silver alloys. The inventors hypothesize that the addition of lanthanum facilitates the formation of fine, dispersed La-rich strengthening phases in the alloy microstructure, significantly improving the strength and hardness of the silver alloy. The resulting product is referred to as a lanthanum-containing silver alloy, with a La weight percentage of 0.01–1 wt% based on the total weight of the lanthanum-containing silver alloy. This lanthanum-containing silver alloy has the composition shown in formula (1):
[0062] Cu x La y Ag bal (1);
[0063] In formula (1), x is the weight percentage of Cu, which is 4 to 14 wt%; y is the weight percentage of La, which is 0.01 to 1 wt%; and bal indicates that Ag is in the balance.
[0064] This application includes the following steps:
[0065] 1) Prepare raw materials of pure silver, pure copper, and lanthanum metal according to the composition of the silver alloy containing lanthanum;
[0066] 2) Melt pure silver and pure copper at 800-970℃ and remove surface slag to obtain a preliminary melt; add lanthanum metal to the preliminary melt, then raise the temperature to 850-1100℃ and hold at 850-1100℃ for 30-70 minutes to obtain a final melt; cast the final melt to obtain an alloy ingot.
[0067] 3) The alloy ingot obtained above is hot-extruded at 400–550°C, an extrusion ratio of 6–10:1, and an extrusion rate of 4–9.5 mm / min to obtain the lanthanum-containing silver alloy. Detailed parameters are as described above and will not be repeated here.
[0068] The testing method is described below:
[0069] SEM testing: Tested using a German Zeiss-SIGMA500 cold field emission scanning electron microscope.
[0070] XRD testing: The test was conducted using a Panaco X-pertpowder X-ray diffractometer from the Netherlands.
[0071] Yield strength test: An Instron 5982 universal testing machine was used, in accordance with GB / T228.1-2021 Metallic materials, tensile testing - Part 1: Test method at room temperature.
[0072] Hardness testing: Brinell hardness was tested using a NEMESIS 9100 hardness tester from the Netherlands.
[0073] Example 1
[0074] In this embodiment, the lanthanum-containing silver alloy has the chemical composition shown in formula (1): Cu x La y Ag bal (1); In formula (1), x is the weight percentage of Cu element, x is 7wt%; y is the weight percentage of La element, y is 0.2wt%; bal indicates that Ag element is the balance.
[0075] The preparation method of this lanthanum-containing silver alloy is as follows:
[0076] 1) Prepare raw materials, namely pure silver ingots, pure copper ingots, and lanthanum metal, according to the composition of the silver alloy containing lanthanum. Dry and preheat the above raw materials at 200℃ for 1 hour, and set aside for later use.
[0077] 2) Place the preheated pure silver and pure copper ingots in a resistance furnace and heat to 850°C until they are completely melted. Remove the surface slag to obtain a preliminary melt. Add preheated lanthanum metal to the preliminary melt, then raise the temperature to 950°C and stir until the lanthanum metal is completely dissolved. Then hold at 950°C for 60 minutes to obtain a final melt. Pour the final melt into a casting mold preheated to 300°C and allow it to cool naturally to obtain an alloy ingot.
[0078] 3) The obtained alloy ingot was hot-extruded at 450℃, an extrusion ratio of 8:1, and an extrusion rate of 6 mm / min to obtain a silver alloy containing lanthanum. The product is designated as Cu7La. 0.2 Ag bal .
[0079] Comparative Example 1
[0080] In this comparative example, the silver alloy does not contain lanthanum. The silver alloy has the following composition: The silver alloy has the chemical composition shown in formula (2): Cu x Ag bal (2); In formula (2), x is the weight percentage of Cu element, x is 7wt%; bal indicates that Ag element is in the balance.
[0081] The preparation method of this silver alloy is as follows:
[0082] 1) Prepare raw materials, pure silver ingots and pure copper ingots, according to the composition of the silver alloy. Dry and preheat the above raw materials at 200℃ for 1 hour, and set aside for later use.
[0083] 2) Place the preheated pure silver and pure copper ingots in a resistance furnace and heat to 850°C to completely melt them. Remove the surface slag to obtain a preliminary melt. Then raise the temperature to 950°C and hold at 950°C for 60 minutes to obtain the final melt. Pour the final melt into a casting mold preheated to 300°C and allow it to cool naturally to obtain an alloy ingot.
[0084] 3) The obtained alloy ingot was hot-extruded at 450℃, an extrusion ratio of 8:1, and an extrusion rate of 6 mm / min to obtain a silver alloy. The product is designated as Cu7Ag. bal .
[0085] Comparative Example 2
[0086] In this comparative example, the silver alloy containing lanthanum has the chemical composition shown in formula (1): Cu x La y Ag bal(1); In formula (1), x is the weight percentage of Cu element, x is 2wt%; y is the weight percentage of La element, y is 2wt%; bal indicates that Ag element is the balance.
[0087] The preparation method of this lanthanum-containing silver alloy is the same as in Example 1. The product is designated as Cu2La2Ag. bal .
[0088] Experimental Example
[0089] (I) The SEM results of the extruded silver alloy containing lanthanum obtained in Example 1 are shown in [the figure]. Figure 1 The XRD results are shown in Figure 2 .Depend on Figure 1 It can be seen that the second phase of the obtained lanthanum-containing silver alloy is finely and diffusely distributed on the silver matrix. (From...) Figure 2 It can be seen that the alloy structure mainly contains α-Ag matrix phase and β-Cu second phase.
[0090] (II) The test results of yield strength and hardness of the silver alloy containing lanthanum obtained in Example 1 and Comparative Example 2, and the silver alloy of Comparative Example 1 are shown in Table 1.
[0091] Table 1
[0092] serial number The product is recorded as Yield strength (MPa) Hardness (HBW) Example 1 <![CDATA[Cu7La 0.2 At bal ]]> 240 112 Comparative Example 1 <![CDATA[Cu7Ag bal ]]> 198 106 Comparative Example 2 <![CDATA[Cu2La2Ag bal ]]> 205 105
[0093] As shown in Table 1, the lanthanum-containing silver alloy of the present invention has higher yield strength and hardness.
[0094] This invention is not limited to the above-described embodiments. Any modifications, improvements, or substitutions that can be conceived by those skilled in the art without departing from the essential content of this invention fall within the scope of this invention.
Claims
1. A silver alloy containing lanthanum, characterized in that, It has the chemical composition shown in formula (1): With x to y Ag bal (1); In formula (1), x is the weight percentage of Cu, which is 4 to 14 wt%; y is the weight percentage of La, which is 0.01 to 1 wt%; and bal indicates that Ag is the balance.
2. The lanthanum-containing silver alloy according to claim 1, characterized in that, x is 5–12 wt%, and y is 0.05–0.8 wt%.
3. The lanthanum-containing silver alloy according to claim 1, characterized in that, x is 5–10 wt%, and y is 0.1–0.6 wt%.
4. The lanthanum-containing silver alloy according to claim 1, characterized in that, x is 5.5–8.5 wt%, and y is 0.1–0.5 wt%.
5. The lanthanum-containing silver alloy according to claim 1, characterized in that, x is 6–8 wt%, and y is 0.15–0.35 wt%.
6. The method for preparing the lanthanum-containing silver alloy according to any one of claims 1 to 5, characterized in that, Includes the following steps: 1) Prepare raw materials of pure silver, pure copper, and lanthanum metal according to the composition of the silver alloy containing lanthanum; 2) Melt pure silver and pure copper at 800-970℃ and remove surface slag to obtain a preliminary melt; add lanthanum metal to the preliminary melt, then raise the temperature to 850-1100℃ and hold at 850-1100℃ for 30-70 minutes to obtain a final melt; cast the final melt to obtain an alloy ingot. 3) The obtained alloy ingot is hot-extruded at 400-550℃, extrusion ratio of 6-10:1, and extrusion rate of 4-9.5 mm / min to obtain the silver alloy containing lanthanum.
7. The preparation method according to claim 6, characterized in that, Between step 1) and step 2), the following steps are also included: preheating pure silver, pure copper and lanthanum metal at 180-270℃ for 30-70 minutes respectively to obtain preheated pure silver, pure copper and lanthanum metal respectively.
8. The preparation method according to claim 6, characterized in that, In step 2), before casting the final melt into the casting mold, the casting mold is preheated to 250-350°C.
9. The preparation method according to claim 6, characterized in that, In step 3), the extrusion ratio is 7 to 9:1 and the extrusion rate is 5 to 8.5 mm / min.
10. Uses of lanthanum metal in improving the yield strength and hardness of silver alloys.
Citation Information
Patent Citations
Sliding contact point material and method for manufacturing same
CN107109530A
Active brazing filler metal for sealing sapphire and kovar alloy and preparation method of active brazing filler metal
CN119426846A
AgCuNi multi-element brazing filler metal as well as preparation method and brazing process thereof
CN119772450A